Synthesis of carbonylated heteroaromatic compounds via visible-light-driven intramolecular decarboxylative cyclization of o-alkynylated carboxylic acids. Issue 61 (13th July 2017) - Gao, Fei; Wang, Jiu-Tao; Liu, Lin-Lin; Ma, Na; Yang, Chao; Gao, Yuan; Xia, Wujiong
Abstract : An efficient strategy for the easy access to carbonylated heteroaromatic compounds has been developed via a visible-light-promoted intramolecular decarboxylative cyclization reaction of o -alkynylated carboxylic acids. Abstract : An efficient strategy for the easy access to carbonylated heteroaromatic compounds has been developed via a visible-light-promoted intramolecular decarboxylative cyclization reaction of o -alkynylated carboxylic acids. This method is characterized by its benign conditions and the tolerance to a wide range of functionalities.